A post-foundational Practical Theology? The pastoral cycle and local theology - Macallan, Brian; Hendriks, Jurgens (Nederduitse Gereformeerde Teologiese Tydskrif, 2013)
The article argues that Practical Theology has moved from the uncertainty of simply being applied theology to a point where its methodology, here described as the pastoral cycle, has gained such confidence, that it is seen as the natural way of doing theology. This shift in confidence occurred because the inherent theological and epistemological fault lines in foundationalism are no longer obscure. The article defines foundationalism but then concentrate on describing the local and glocal dimensions of the pastoral cycle as well as the importance of doing it in an interdisciplinary way.